A Diffusion Tensor Imaging Study on the White Matter Structures Related to the Phonology in Cantonese–Mandarin Bilinguals - Xu, Xiaoyu; Jin, Yuying; Pan, Ning; Cao, Muqing; Jing, Jin; Ma, Jingwen; Fan, Xiaoxuan; Tan, Si; Song, Xiaojing; Li, Xiuhong (Frontiers in Human Neuroscience, 2022)
Both Cantonese and Mandarin are logographic languages, and phonology is the main difference between the two languages. It is unclear whether the long-term experience of Cantonese-Mandarin bilingualism will shape different brain white matter structures related to phonological processing. 30 Cantonese-Mandarin bilinguals and 30 Mandarin monolinguals completed diffusion-weighted imaging (DWI) scan and phonological processing tasks. The tractography and TBSS were used to investigate the structural differences in the bilateral superior longitudinal fasciculus (SLF), inferior longitudinal fasciculus (ILF) and inferior fronto-occipital fasciculus (IFOF) between Cantonese-Mandarin bilinguals and Mandarin monolinguals. Post-hoc correlation analysis was conducted to investigate the relationship between the different structures with phonological processing skills. Compared to the Mandarin monolinguals, the Cantonese-Mandarin bilinguals had higher fractional anisotropy (FA) along the left ILF, higher mean diffusivity (MD) along the right IFOF and the temporoparietal segment of SLF (tSLF), higher axial diffusivity (AD) in the right IFOF and left ILF, and lower number of streamlines in the bilateral tSLF. The mean AD of the different voxels in the right IFOF and the mean FA of the different voxels in the left ILF were positively correlated with the inverse efficiency score (IES) of the Cantonese auditory and Mandarin visual rhyming judgment tasks respectively within the bilingual group. The correlation between FA and IES was different between the groups. Long-term experience of Cantonese-Mandarin bilinguals shapes different brain white matter structures in tSLF, IFOF and ILF. Compared to the monolinguals, the bilinguals’ white matter showed higher diffusivity, especially in the axonal direction. These changes were related to bilinguals’ phonological processing.